MONTREAL COGNITIVE ASSESSMENT (MoCA): A CONVERGENT VALIDATION STUDY IN THE FRAMEWORK OF A NEUROPSYCHOLOGICAL ASSESSMENT CONSULTATION - Artiaga, Ana Carolina Machado (2021)
Dissertação de Mestrado em Neuropsicologia Clínica e Experimental apresentada à Faculdade de Psicologia e de Ciências da Educação